Effect of age and diet composition on activity of pancreatic enzymes in birds - Brzek, Pawel (2013)
Digestive enzymes produced by the pancreas and intestinal epithelium cooperate closely during food hydrolysis. Therefore, activities of pancreatic and intestinal enzymes processing the same substrate can be hypothe- sized to change together in unison, as well as to be adjusted to the concentration of their substrate in the diet. However, our knowledge of ontogenetic and diet-related changes in the digestive enzymes of birds is limited mainly to intes- tinal enzymes; it is largely unknown whether they are accompanied by changes in activities of enzymes produced by the pancreas. Here, we analyzed age- and diet-related changes in activities of pancreatic enzymes in five pas- serine and galloanserine species, and compared them with simultaneous changes in activities of intestinal enzymes. Mass-specific activity of pancreatic amylase increased with age in young house sparrows but not in zebra finches, in agreement with changes in typical dietary starch content and activity of intestinal maltase. However, we found little evidence for the presence of adaptive, diet-related modu- lation of pancreatic enzymes in both passerine and gal- loanserine species, even though in several cases the same birds adaptively modulated activities of their intestinal enzymes. In general, diet-related changes in mass-specific activities of pancreatic and intestinal enzymes were not correlated. We conclude that activity of pancreatic enzymes in birds is under strong genetic control, which enables evolutionary adjustment to typical diet composi- tion but is less adept for short term, diet-related flexibility.